Multi-Decadal to Short-Term Beach and Shoreline Mobility in a Complex River-Mouth Environment Affected by Mud From the Amazon - Jolivet, Morgane; Anthony, Edward J.; Gardel, Antoine; Brunier, Guillaume (Frontiers in Earth Science, 2019)
On the 1500 km-long mud-dominated Guianas coast of South America, between the mouths of the two mega-rivers, the Amazon and the Orinoco, debouch numerous small rivers draining the humid tropical/equatorial Guiana Shield. The geomorphic development of the mouths of these rivers reflects interactions among water discharge, fluvial sediment load, and the alongshore migration of Amazon-derived mud banks alternating with inter-bank areas. The mouth of the Maroni River, astride the French Guiana-Suriname border, shows advanced estuarine infill and geomorphic development characterized by a western (downdrift) side comprising numerous recent cheniers and an eastern (updrift) side bound by an old (> 2000 years B.P.) chenier. A multi-decadal analysis of the beach bounding this chenier shows little net overall mobility notwithstanding significant decadal to sub-decadal variation. The overall stability reflects the diversion of sand supply from the Maroni River towards the downdrift coast and limited sand supply by the smaller Mana River further east, and the south bank of which was contiguous with this beach. The variability in beach multi-decadal mobility reflects the influence, on waves, of alongshore-migrating banks (strong wave dissipation, limited beach mobility) and inter-bank areas (limited wave dissipation, larger beach mobility), highlighted by a comparison, in the current bank phase, of offshore and inshore waves. Erosion of the beach between 2011 and 2017 coincides with the sealing of the mouth of the Mana by muddy progradation in 2011 and mouth relocation several kilometers eastward. The morphodynamics of the beach and shorter-term fluctuations in budget are related to: (1) interaction with estuarine sand dunes mobilized by strong tidal currents on the adjacent shallow shoreface, (2) the influence of the Maroni channel, and (3) rapid encroachment of the leading edge of the shore-attached mud bank on the eastern part of the beach. The beach morphodynamics and evolution highlight, thus, embedded levels of influence: the Maroni at the local scale, and the net westward sediment-transport system and bank and inter-bank alternations that affect the Guianas coast at a regional scale. The recent erosion poses a threat to the local communities by reducing beach space available for recreation and turtle-nesting.